Satellite Image Identification of Wind Channels to Delineate Wind Energy Generation Sites in Pakistan - Zeeshan Alam Nayyar,; Nayyer Alam Zaigham, (Journal of Basic & Applied Sciences, 2014)
Technologically, all the renewable energy sources are viable and consequently suit to efforts for poverty alleviation and cleaner environment in Pakistan. They can play an important role in meeting the challenge of providing future electricity to all parts of the country. Wind energy is one of these renewable sources. Considering the geological & geomorphologic setup, geographical position and climatic cycles, Pakistan has tremendous wind potential. Pakistan has about 1000 km long coastline, which could be utilized for the installation of wind farms and wind-monitoring stations as well. Various preliminary comparative studies apparently show that the wind potential is not uniformly distributed along the coastal belt of Pakistan. The present research study is based on the analyses of the satellite images of different periods. On the bases of the result of the study, the prospective wind channels have been identified all along the coastal belt of Pakistan, which are the ideal regions to establish the wind farms for the generation of electricity on the commercial scale.